Serum Vascular Endothelial Growth Factor (VEGF) levels in patients with alpha thalassemia - esmaeili, samira (Archives of Medical Laboratory Sciences, 2019)
Background: Alpha-thalassemia syndrome includes a group of hereditary anemia in which expression of alpha globin chains is decreased or absent. Impaired RBC in patients with thalassemia causes vessel involvement and endothelial cell vessel disturbance. Vascular Endothelial Growth Factor (VEGF) is the most important regulator for endothelial cell proliferation. So, the aim of this study is to compare the serum VEGF levels in patients with alpha thalassemia and normal control group. Materials and Methods: This case-control study was conducted on 17 patients with alpha thalassemia and 40 healthy people. Serum VEGF levels were measured by enzyme-linked immune sorbent assay (ELISA) kit. Then statistical analysis of results were performed using SPSS 16, value of P <0.05 was considered statistically significant. Results: Mean serum VEGF levels in case and control groups were 2294.19±1552.39 and 598.09±988.17pg/ml, respectively. Serum VEGF levels were higher in patients with alpha thalassemia (P <0.01). There was no significant correlation between serum VEGF levels and Hemoglobin. (P= 0.73). Conclusion: Our study revealed that patients with alpha thalassemia have elevated levels of serum VEGF than normal control group. Further studies with larger sample size are recommended to confirm these observations.